Stress Level of General Dentists and Pedodontists in Dental Treatment of Pediatric Patients - Meshki, Razie; Salehian, Niloofar; Tehrani, Sahar (Galen Medical Journal, 2024)
Background: This study aimed to assess the stress level of general dentists and pedodontists in dental treatment of pediatric patients. Materials and Methods: This cross-sectional study was conducted on 101 general dentists and 93 pedodontists who were selected from different provinces of Iran by stratified random sampling. A researcher-designed questionnaire was used for data collection, which included four sections of demographics, trait stress, functional stress, and attitude towards the efficacy of behavioral control measures for pediatric dental patients. Data were analyzed by ANOVA, Bonferroni test, Chi-square test, and independent t-test. Results: The mean age of the participants was 37.93 years. The participants reported the highest level of stress during administration of an inferior alveolar nerve (IAN) Block for anxious children, and the lowest stress during cavity preparation for an amalgam restoration of a mandibular tooth. In all procedures, pedodontists reported lower stress level than general dentists; except for the Distraction technique, Modeling technique, presence of child’s parents, and examination of child (P>0.05). The stress level of males was lower than females during administration of an IAN Block (P<0.05). The highest efficacy score was given to the Tell-Show-Do technique and the lowest score was allocated to the hand-over-mouth technique. The attitude of pedodontists was more positive than general dentists regarding the efficacy of behavioral control techniques. Conclusion: The results showed that administration of an IAN block for an anxious child was the most stressful procedure for both general dentists and pedodontists. The stress level of pedodontists was generally lower than that of general dentists in all procedures.